PENYELESAIAN SENGKETA MEREK TERKENAL ANTARA IKEA SWEDIA DAN IKEA INDONESIA DI MAHKAMAH AGUNG BERDASARKAN HUKUM INTERNASIONAL - Sonang Akbario; Abdul Rahman; Jelly Leviza (Journal of USU International Law, 2018)
ABSTRACT Abdul Rahman, S.H., M.H.* Dr. Jelly Leviza, S.H., M.Hum ** Sonang Akbario ***   Trademarks as part of copyright, especially well-known marks, had an important role as the identity of a trade goods and service. Legal protection for rights of marks is regulated in National Law number 15 of 2001 concerning Trademarks and has been replaced by new regulation, Law number 20 of 2016 concerning Trademarks and Geographical Indications. The rights holder obtain to take legal protection on the marks have been made at the Directorate General of Intellectual Property Rights. This sturdy raised issues between well-known marks with local marks that have similarity in name, this sturdy was conducted at IKEA from Sweden against local Ikea marks owned by PT.Ratania Khatulistiwa from Surabaya which had been cut to the cassation level. This sturdy method uses normative juridicial method with descriptive research spesifications. The methods used and data access are carried out information through library research or also secondary data containing primary, secondary and tertiary materials related to this subject matter. The results of the sturdy show that the regulation of well-known marks according to International Law is contained in the Article 6 bis Paris Convention and Article 16 paragraph 2 of the TRIPS Agreement, and the Indonesian National Law, based on article 6 paragraph 1 (b) of Law number 15 of 2001 concerning Trademarks and article 21 paragraph 1 (b) Law number 20 of 2016 concerning Trademarks and Geographical Indications. Paris Convention and TRIPS Agreement reject the registration of application marks that have similarities with well-known marks. Indonesian national law number 15 of 2001 and law number 20 of 2016 also rejects the registration of marks that have similarities principally with well-known marks for similar goods and services. The dispute resolution for the Ikea marks in Central Jakarta District Court of Indonesia abolished the Swedish IKEA trademark rights and this decision was strengthened by the Supreme Court’s decision on the grounds that the marks was not used by it’s owner for 3 consecutive years can be removed from the General Register of Marks according with article 61 paragraph 2 of law number 15 of 2001 amd artice 74 paragraph 1 of law number 20 of 2016, the principle of non-use also contained in the provisions of the International Law precisely at Article 19 paragraph 1 of the TRIPS Agreement Keywords : Well-known Marks, Ikea, Paris Convention and TRIPS Agreement  *      Supervisor Lecturer I Faculty of Law University of  North Sumatera **     Supervisor Lecturer II Faculty of  Law  University of  North Sumatera ***  Student of  Faculty of  Law University of  North Sumatera